S75 Is a practice incremental shuttle walk test always necessary and is it influenced by MRC dyspnoea grade?. (16th November 2010) - Dhaliwal, A K; Sewell, L; Collier, R; Singh, S J
Abstract : Introduction: The Incremental Shuttle Walk Test (ISWT) is a common assessment tool used to assess exercise capacity in patients with Chronic Obstructive Pulmonary Disease (COPD). Healthcare professionals conducting this test will ask patients to perform a practice Incremental Shuttle Walk Test (PISWT). The aim was to explore whether a PISWT is needed and to examine whether variance between PISWT and the second shuttle walk test (ISWT2) is influenced by MRC dyspnoea grade. Method: This is a retrospective audit of 441 COPD patients: male 194 female 297 mean (SD) age 68.9 (10.13) years who were assessed for outpatient pulmonary rehabilitation (PR). Patients undertook a PISWT and rested for 30 min before performing ISWT2. Distance covered (m), MRC grade, heart rate (HR), forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC) and body mass index (BMI) were recorded. Results: The mean (SD) change between both shuttle walk tests and significance levels were analysed using a paired t test. These results are detailed in Abstract S75 Table 1 . Overall, there was a statistically significant increase in mean walking distance between PISWT and ISWT2. In each patient subgroup, a significant increase was seen for all, except for those of MRC grade 1; however this group consisted only of eight patients. Furthermore, no patient subgroup achieved the minimum clinically important distance for the ISWT >47.5 m (Singh et al, 2008). Patients in MRC grades 2 and 3 showed more variance between each shuttle walk test. The least mean change was seen in patients of MRC grade 5. Conclusion: Overall, there was a statistical significant increase in distance walked in all patients. These data confirm the need for a PISWT to be conducted within the COPD population. Patients in MRC grades 2 and 3 show a larger variance in walking distance between both shuttle walk tests.